Correlation between crystal structure and magnetism in PLD grown epitaxial films of ε-Fe2O3 on GaN. Issue 1 (31st December 2021) - Suturin, Sergey M.; Korovin, Alexander M.; Sitnikova, Alla A.; Kirilenko, Demid A.; Volkov, Mikhail P.; Dvortsova, Polina A.; Ukleev, Victor A.; Tabuchi, Masao; Sokolov, Nikolai S.
ABSTRACT: In the present paper we discuss correlations between crystal structure and magnetic properties of epitaxial ε-Fe2 O3 films grown on GaN. The large magnetocrystalline anisotropy and room temperature multiferroic properties of this exotic iron oxide polymorph, make it a perspective material for the development of low power consumption magnetic media storage devices. Extending our recent progress in PLD growth of ε-Fe2 O3 on the surface of technologically important nitride semiconductors, we apply reciprocal space tomography by electron and x-ray diffraction to investigate the break of crystallographic symmetry occurring at the oxide-nitride interface resulting in the appearance of anisotropic crystallographic disorder in the sub-100 nm ε-Fe2 O3 films. The orthorhombic-on-hexagonal nucleation scenario is shown responsible for the development of a peculiar columnar structure observed in ε-Fe2 O3 by means of HRTEM and AFM. The complementary information on the direct and reciprocal space structure of the columnar ε-Fe2 O3 films is obtained by various techniques and correlated to their magnetic properties. The peculiar temperature dependence of magnetization studied by the small-field magnetization derivative method and by neutron diffraction reveals the existence of a magnetic softening below 150 K, similar to the one observed earlier solely in nanoparticles. The magnetization reversal in ε-Fe2 O3 films probed by X-ray magnetic circular dichroism is found different from the behavior of the bulk averaged magnetization measured by conventional magnetometry. The presented results fill the gap between the numerous studies performed on randomly oriented ε-Fe2 O3 nanoparticles and much less frequent investigations of epitaxial epsilon ferrite films with lattice orientation fixed by the substrate. Graphical abstract: uf0001